1994
DOI: 10.3109/02813439409029247
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal application of lactobacilli in the prophylaxis of recurrent lower urinary tract infection in women

Abstract: It is still uncertain whether vaginal application of lactobacilli reduces the infection rate in cystitis-prone women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 12 publications
2
27
0
4
Order By: Relevance
“…In preliminary, uncontrolled studies, Bruce et al [23] demonstrated reduced UTI attack rates when H 2 O 2 -negative lactobacilli were introduced into the vagina. However, not all investigators have enjoyed similar success [24]. Further studies are needed with large number of subjects and carefully defined and selected Lactobacillus strains.…”
Section: Urinary Tract Infections In Womenmentioning
confidence: 84%
“…In preliminary, uncontrolled studies, Bruce et al [23] demonstrated reduced UTI attack rates when H 2 O 2 -negative lactobacilli were introduced into the vagina. However, not all investigators have enjoyed similar success [24]. Further studies are needed with large number of subjects and carefully defined and selected Lactobacillus strains.…”
Section: Urinary Tract Infections In Womenmentioning
confidence: 84%
“…Reid et al have demonstrated that Lactobacillus vaginal suppositories are safe and may be effective in reducing the recurrence of UTI [10]. Conversely, Baerheim et al have demonstrated that uncertainty exists as to whether the vaginal application of lactobacilli reduces the infection rate in cystitis-prone women [11]. Since the effectiveness of Lactobacillus vaginal suppositories on recurrent UTI is still inconclusive, a prospective clinical study to confirm the safety and effectiveness of Lactobacillus vaginal suppositories against recurrent UTI was performed.…”
Section: Discussionmentioning
confidence: 97%
“…However, the effectiveness of Lactobacillus vaginal suppositories on recurrent UTI is still inconclusive [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…McGroarty (1993) and Parent et al (1996) outlined some of the characteristics that probiotics for the urogenital tract should have, most of them referring to technological properties. Some experiments and assays reported on the prevention of urinary tract infections (Baerheim et al, 1994;Reid et al, 1992), and others referred to the vaginal tract. Hilton et al (1995) mentioned the use of Lactobacillus GG isolated from the gastrointestinal tract, topically applied to the treatment of recurrent vaginitis.…”
Section: Discussionmentioning
confidence: 99%